The social work supervisor : supervision in community, day care, and residential settings - Brown, Allan G. 4 0 16; 1955- Bourne, Iain; 5 (Buckingham ;;Philadelphia : Open University Press, 1996)
The Social Work Supervisor is the first comprehensive British text on supervision of staff in social work, community care and social welfare settings. It examines the changing social work scene of the 1990s, and breaks new ground in areas such as anti-oppressive supervision, supervision of post-traumatic stress, and group supervision. The Social Work Supervisor is a comprehensive text for the social work supervisor, and for all supervisors in social welfare and community care settings. It includes new material not found in other books on supervision. The authors emphasize the importance of the supervisory relationship, regular skilled supervision and a clear value base in the provision of good quality services. This book provides a clear theoretical framework, bringing theory and practice together through numerous practical examples of supervision in action. One major chapter examines a range of typical supervision situations, and provides suggestions for possible supervisor responses. The Social Work Supervisor will be invaluable reading for new and experienced supervisors; practice-teachers supervising students; trainers of supervisors; and social work managers.--BOOK JACKET.
Includes bibliographical references (p. [184]-188) and index.
Keywords: 2 -- 0; 6; Supervision of.;Administration.;Administration.;Administration. -- Social workers;Home care services;Day care centers;Group homes -- 20; 20; 2